2019 International Joint Conference on Neural Networks (IJCNN) 2019
DOI: 10.1109/ijcnn.2019.8852075
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised Domain Adaptation using Graph Transduction Games

Abstract: Unsupervised domain adaptation (UDA) amounts to assigning class labels to the unlabeled instances of a dataset from a target domain, using labeled instances of a dataset from a related source domain. In this paper we propose to cast this problem in a game-theoretic setting as a non-cooperative game and introduce a fully automatized iterative algorithm for UDA based on graph transduction games (GTG). The main advantages of this approach are its principled foundation, guaranteed termination of the iterative algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…Additionally, Table 3 compares UFAL to SOTA methods on the Office-Caltech dataset. Again, we surpass recently proposed methods such as GTDA+LR [32] and RWA [31]. UFAL even outperforms the ensemble based algorithm of Rakshit et al [29] by 0.5%.…”
Section: Resultsmentioning
confidence: 54%
“…Additionally, Table 3 compares UFAL to SOTA methods on the Office-Caltech dataset. Again, we surpass recently proposed methods such as GTDA+LR [32] and RWA [31]. UFAL even outperforms the ensemble based algorithm of Rakshit et al [29] by 0.5%.…”
Section: Resultsmentioning
confidence: 54%
“…Furthermore, Zhang et al [6] and Wang et al [7] combined the techniques in both branches. Vascon et al [8] and Wulfmeier et al [9] suggested a new technique for the UDA problem using Nash equilibrium [10] and Generative Adversarial Networks (GAN) [11], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The GTG has been succesfully applied in many different SSL contexts, like deep metric learning [10], matrix factorization [37], image recognition [2], proteinfunction prediction [39] and, indeed, traditional text-based WSD setting [36]. Moreover, it works consistently better [38] than other graph-based SSL methods like Label Propagation [41] and Gaussian Fields [42].…”
Section: Introductionmentioning
confidence: 99%